Immediate response of paddy soil microbial community and structure to moisture changes and nitrogen fertilizer application - Han, Linrong; Qin, Hongling; Wang, Jingyuan; Yao, Dongliang; Zhang, Leyan; Guo, Jiahua; Zhu, Baoli (Frontiers in Microbiology, 2023)
Water and fertilizer managements are the most common practices to maximize crop yields, and their long-term impact on soil microbial communities has been extensively studied. However, the initial response of microbes to fertilization and soil moisture changes remains unclear. In this study, the immediate effects of nitrogen (N)-fertilizer application and moisture levels on microbial community of paddy soils were investigated through controlled incubation experiments. Amplicon sequencing results revealed that moisture had a stronger influence on the abundance and community composition of total soil bacteria, as well as ammonia oxidizing-archaea (AOA) andbacteria (AOB). Conversely, fertilizer application noticeably reduced the connectivity and complexity of the total bacteria network, and increasing moisture slightly exacerbated these effects. NH4 + -N content emerged as a significant driving force for changes in the structure of the total bacteria and AOB communities, while NO3 --N 2 content played more important role in driving shifts in AOA composition. These findings indicate that the initial responses of microbial communities, including abundance and composition, and network differ under water and fertilizer managements. By providing a snapshot of microbial community structure following short-term N-fertilizer and water treatments, this study contributes to a better understanding of how soil microbes respond to long-term agriculture managements.